PHARMACOLOGICAL PROPERTIES OF ACTIVE SUBSTANCES IN THE SALIVA OF THE HIRUDO MEDICINALIS LEECH (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Medical leeches Hirudo medicinalis are used in medicine in a procedure known as hirudotherapy, which involves the external use of leeches to treat various diseases. The components of leech saliva are believed to help reduce inflammation, thin the blood, and improve circulation. Today, it is of greatest relevance to study the composition of the saliva of medicinal leeches, since if it is proven that specific components of saliva have medicinal properties, this may lead to the development of new drugs or therapeutic methods.